PEMANFAATAN LAHAN PEKARANGAN DENGAN BUDIDAYA TANAMAN BUAH DALAM POT (TABULAMPOT) DI DESA GESIK KECAMATAN TENGAH TANI KABUPATEN CIREBON - Trisnaningsih, Umi; Wahyuni, Siti; Wachdijono, Wachdijono (Qardhul Hasan: Media Pengabdian kepada Masyarakat, 2021)
Fruit cultivation in pots is a solution for people who want to grow fruit in a narrow yard, such as in Gesik Village, Tengah Tani District, Cirebon Regency. The training was held with the aim of increasing the knowledge and skills of the members of the Gesik Village Empowerment and Family Welfare Mover Team in the cultivation of fruit plants in a pot. The training consisted of counseling activities and demo/practice of fruit plant cultivation. The activity was held at the Gesik Village Hall on January 25 and February 1, 2020, which was attended by 25 participants. The participants were divided into groups based on their respective RW. Each group is tasked with planting and maintaining one type of fruit plant. To find out the development of plants, monitoring is carried out on 8 and 10 February 2020. At the time of monitoring, fertilizer practice is carried out on fruit plants in a pot. The results of the activity showed that the participants could practice the cultivation and maintenance of fruit plants in pots.